PERIPHERAL LYMPHOCYTE SUB – POPULATIONS ANALYSIS IN HYDATIDOSIS PATIENTS WITH DIFFERENT CLINICAL PARAMETERS - Al-Qadhi, Ban; Al-Jeboori, Tariq; Al-Bashir, Nada (Iraqi Journal of Science, 2024)
Lymphocyte sub-population analysis had been done by indirect and direct immunostaining (CD-markers) technique for eighty- two hydatidosis patients with different clinical parameters. This technique showed, a significant decrease in percentage of CD3, CD4 cells in hydatidosis patients compared to healthy control group,while the results showed that the level of CD8 cells was higer than the control group. The CD4/ CD8 ratio was lower in hydatidosis patients in comparison to the control group.Furthermore, the percentage of CD14 cells of hydatidosis patients was significantly lower than that of the control group,and there was insignificant increase in CD22 of hydatidosis patients in comparison to that of control group.In general,this study showed that there was no significant difference in all types of CD cells percentage between hydatidosis patients in relation to different clinical parameters,except in relation to the size of the cysts.